The degree to which public school principals in East Jerusalem practice managing school crises from the teacher’s perspective - Nasrala, Lubna El-Tamimi; Agbaria, Mervat Abu Asab; Abu-Asbah, Khaled (Journal of Educational and Psychological Sciences, 2021)
This study aimed to know the reality of crisis management among public school principals in East Jerusalem from the teachers ’point of view, and the research was based on the descriptive and analytical approach, and the Nieroch questionnaire (2020) was used with some changes to demographic variables to suit the current study. A random sample was chosen a sample consisting of (233) male and female teachers. The results showed that the degree of practicing public school principals in East Jerusalem in managing school crises got an average (3.58 out of 5), meaning a degree of (high) practice. At the level of domains, the confrontational field before the crisis occurred got the highest average (3.64 out of 5), then the confrontation field. During the occurrence of the crisis at an average of (3.58), and finally the confrontation after its occurrence at an average of (3.52), all of which are of a (high) practice rating, and that school principals have a preconceived perception of any emergency crisis and on all axes of the questionnaire (before, during and after the crisis). The study also found that the ability Managers deal with the crisis before its occurrence is greater than dealing with it after its end, and the study indicated that there are statistically significant differences in the degree of school crisis management among public school principals due to the variables of the teacher’s gender and the gender of the school principal and in favor of males. Based on the results, the researchers presented a set of recommendations and proposals to enhance the culture of crisis management among public school principals in East Jerusalem, all of Palestine and the Arab countries.